AB0798 High Rates of Work Disability in Patients with Psoriatic Arthritis. (9th June 2015) - De Gaspari, C.N.; Goldeinstein-Schainberg, C.; Pretti, F.Z.; Silva, T.C.P.; Gonçalves, C.R.; Sampaio-Barros, P.D.; Saad, C.G.S.; Moraes, J.C.B.
Abstract : Background: Aggressive joint involvement allied to disease activity and comorbidities contribute to physical and psychosocial impairment of patients with psoriatic arthritis (PsA).Therefore, total expenses involved in psoriatic disease management may be elevated, considering that both direct and indirect costs related to multidisciplinary therapy, functional incapacity and loss of productivity may lead to an important socioeconomic impact. Objectives: To evaluate labor status, to determine employment rate and the prevalence of work disability among patients with PsA from a single tertiary university center considering some disease features. Methods: PsA patients from our outpatient rheumatology clinic were assesses during a 6 month period. A self-administered questionnaire was applied in order to evaluate demographic parameters, specific clinical and laboratory characteristics of the disease, comorbidities, functional capacity (HAQ score) and labor activity. Student's t-test, Chi-square and Fisher's exact test were used for statistical analyses and P values ≤0.05 were considered significant. Results: Fifty three patients were included, 26 males and 27 females, mean age = 52, 7±13 yrs (19-76 yrs), mean age at diagnosis = 39, 4±14, 4 yrs (15-66 yrs); 57% had arterial hypertension (AH), 30% dyslipidemia and 15% diabetes. All patients had good educational level, 26% completed high school and 19% had a professional degree. At the time of the study, 66% (35/53) were not working; among the latter, 35% (12/35) were retired due to PsA disability, 27% (10/35) retired due to other reasons, 26% (9/35) unemployed, and 12% (4/35) were temporary away from work. The comparison of 35 unemployed vs. 18 employed patients revealed similar age (54, 7yrs vs. 48, 8yrs, P=0.16) and sex ratio. Both groups were also comparable for HAQ (1.1 vs. 0.8, P=0.17) and DAS 28 <3, 5 (19 vs. 14, P=0.15) scores. Frequencies of hypertension (21 vs. 9, P=0.48), dyslipidemia (12 vs. 4, P=0.36), diabetes (4 vs. 4 P=0.42), smokers (4 vs. 1, P=0.65) and alcoholics (2 vs 2, P=0.59) were also alike in both groups. The only differences between unemployed and employed patients was that unemployed had higher joint VAS score (2.3 vs. 1.0, P=0.008) and were still on MTX (88% vs 61%, P=0.031) and NSAIDs (86% vs 50%, P=0.009), but neither on HCQ nor SSZ. Moreover, all patients retired due to PsA disability had AH (P<0.001) and all individuals temporary away from work were on biologic therapy (P<0.024). Conclusions: High rates of work disability in 66% PsA patients, mostly those with AH or under MTX, NSAIDs or biological therapy suggests greater severity of their illness, indicating that early effective aggressive treatment is necessary in order to reduce labor incapacity, loss of productivity and socioeconomic burden. References: Psoriatic arthritis: a systematic review, International Journal of Rheumatic Diseases 2010; 13: 300–317. William Tillett et al. Factors influencing work disability in psoriatic arthritis: first results from a large UK multicentre study, Rehumatology, 2014. Walsh et al. Work Productivity Loss and Fatigue in Psoriatic Arthritis, The Journal of Rheumatology 2014. Disclosure of Interest: None declared